The global disease burden of varicella‐zoster virus infection from 1990 to 2019. Issue 6 (7th January 2022) - Huang, Jiaofeng; Wu, Yinlian; Wang, Mingfang; Jiang, Jiaji; Zhu, Yueyong; Kumar, Rahul; Lin, Su
Abstract: Data on the global epidemiology of varicella‐zoster virus infection (VZVI) is limited. This study aimed to investigate the burden of VZVI based on the global burden of disease study 2019 data. The age‐standardized rates, including the incidence, death, disability‐adjusted life years (DALYs), and the estimated annual percentage changes (EAPC) of VZVI were calculated to evaluate the disease burden of VZVI. The global numbers of incident and death cases due to VZVI were 83 963 744 and 14 553, respectively. The age‐standardized incidence rate of VZVI increased slightly all over the world, while the age‐standardized death and DALYs rate decreased from 1990 to 2019 (EAPC = −2.31 and −1.61, respectively). The younger age (<5 years old) and older groups had the highest VZVI burden. The high sociodemographic index (SDI) region had the highest age‐standardized incidence rates in 2019 (1236.28/100 000, 95% uncertainty interval [UI]: 1156.66–1335.50) and the low SDI region had the lowest incidence (1111.24/100 000, 95% UI: 1040.46–1209.55). The age‐standardized death and DALYs rate of VZVI decreased with the increase of SDI. Amongst the 21 geographical regions, the high‐income Asia‐Pacific (1269.08/100 000) region had the highest age‐standardized incidence rate in 2019, while Sub‐Saharan Africa had the highest age‐standardized death and DALYs rate. The global incidence of VZVI has continued to increase in the past 3 decades, while the age‐standardized death and DALYs rates have decreased. More attention should be paid to the younger and older population, as well as low SDI regions. Highlights: The age‐standardized incidence of VZVI has slightly increased, while the age‐standardized death and DALYs rate has significantly decreased. The highest disease burden of VZVI is concentrated in the extremes of age, concentrated in either elderly or children under five. The death and DALYs of VZVI, across different age groups, are negatively associated with the sociodemographic index levels.